Avaliação in vitro da citotoxicidade e ensaio de HET-CAM de formulações contendo ácido retinoico veiculado, ou não, em microcápsulas de K-carragena : In vitro evaluation of cytotoxicity and the HET-CAM assay of formulations containing retinoic acid vehicled, or not, in K-carrageenan microcapsules - Nabarretti, Barbarah Helena, 1987- (2019)
Orientador: Gislaine Ricci Leonardi